Combined continuum mechanics and molecular dynamics approach for uniaxial deformation of a thermoplastic polymer. Issue 1 (25th January 2021) - Bauer, Christof; Pfaller, Sebastian
Abstract: A hybrid molecular dynamics (MD)‐continuum mechanics (CM) method for calculating a molecular system of an amorphous polymer under uniaxial tensile load was developed. In this contribution, the operating principle of this method is introduced and applied to a sample system. Furthermore, the practicability of the hybrid MD‐CM approach is examined.